Sustainability Orientation, Green Innovation Capability, and Competitive Advantage among ASEAN Manufacturing Firms - Fajar Mahendra Putra; Intan Ayu Lestari; Ahmad Firdaus bin Zulkifli (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study examines the relationships between sustainability orientation, green innovation capability, and competitive advantage among manufacturing firms in ASEAN countries. Manufacturing firms face increasing environmental pressure while competing in cost, quality, and speed. Sustainability orientation reflects a strategic commitment to environmental and social goals embedded in organizational decisions. This study positions green innovation capability as a critical mechanism that transforms sustainability orientation into competitive advantage. The study adopts a quantitative explanatory design and synthesizes empirical evidence from prior manufacturing studies in ASEAN economies. Existing findings consistently show that sustainability orientation positively influences firms’ ability to develop green products, green processes, and environmentally efficient operations. Green innovation capability, in turn, strengthens competitive advantage through cost reduction, differentiation, regulatory compliance, and reputation improvement. The results also indicate that green innovation capability plays a mediating role between sustainability orientation and competitive advantage. Firms with strong sustainability orientation achieve superior competitive outcomes when they actively invest in green technologies, green process redesign, and innovation-oriented capabilities. This study contributes to sustainability and strategic management literature by clarifying the capability-based pathway through which sustainability orientation delivers competitive advantage. The findings provide practical guidance for managers to align sustainability strategies with innovation capabilities to strengthen long-term competitiveness in the ASEAN manufacturing context.